Pre-treatment Pain Symptoms Influence Antidepressant Response to Ketamine in Depressive Patients - Lan, Xiaofeng; Zhou, Yanling; Wang, Chengyu; Li, Weicheng; Zhang, Fan; Liu, Haiyan; Fu, Ling; Wu, Kai; McIntyre, Roger S.; Ning, Yuping (Frontiers in Psychiatry, 2022)
Background Pain strongly coexists with depression. Ketamine has great analgesic and antidepressant effects, acting as a promising role in treating depression with pain. Few studies have evaluated impact of pain symptoms on antidepressant effect of ketamine infusions. Thus, present study investigated whether pain symptoms in individuals with depression moderate response to ketamine. Methods One hundred and four individuals with major depressive disorder and bipolar depression received six intravenous infusions of ketamine. The Montgomery–Åsberg Depression Rating Scale (MADRS) was administered at baseline, the next morning after each infusion and 2 weeks (Day 26) after the last infusion. Pain symptoms were collected at baseline using the short-form McGill Pain Questionnaire (SF-MPQ). Results The prevalence of pain in patients with depression was 48.8%. Mix model analyses showed that pre-treatment pain symptoms assessed by each domain of SF-MPQ significantly moderated antidepressant response to six infusions of ketamine from baseline to day 26 (all p < 0.05). Then follow-up simple slopes analyses suggested that all patients across groups showed a significant symptomatic improvement after ketamine infusions (all p < 0.05), and patients with severe pain (across all domains of SF-MPQ) had greater improvement in depressive symptoms than those with mild pain or non-pain (all p < 0.05). Conclusion A significant and rapid improvement in depressive symptoms was observed in patients with depression and pain after ketamine treatment. Ketamine may be a novel and promising antidepressant preferentially for the therapy of depression with severe pain.